Determination of mineral nutrition contents of grape and pistachio cultivars grown as interplanted orchard - Gursoz S.; Gokoglu S.; Ak B.E. (XIV GREMPA Meeting on Pistachios and Almonds, 2010)
In this experiment, the amount of mineral nutrition uptake of Honusu grape and Kirmizi pistachio cultivars which are commonly grown in the same area of Southeastern Turkey was determined. Also, the influences on mineral nutrition uptake of these plants each other grown in the same conditions was compared. In a mixed plant orchard, the amount of N uptake of grape and pistachio differed one of the other depending on the mineral nutrients content of the soil. Although the soil of the orchard had enough amount of K and Ca, it was determined that Honusu grape cultivar and Kirmizi pistachio cultivar could not have enough benefit from K and Ca mineral nutrition. In addition, there was no problem or competitions between plants regarding Cu uptake from the orchard soil, which contained enough amount of Cu. Moreover, depending on P, Fe and Zn content of soil, pistachio plants had more uptake and benefit from the mineral nutrition compared to the grape cultivar. Depending upon Mg content of the soil, Honusu grape cultivar also showed higher uptake and had more benefit from Mg mineral nutrition compared to Kirmizi pistachio cultivar.
14. GREMPA Meeting on Pistachios and Almonds, 2008/03/30-2008/04/04, Athens (Greece)